2005
DOI: 10.1021/jo0501442
|View full text |Cite
|
Sign up to set email alerts
|

Practical Synthesis of the New Carbapenem Antibiotic Ertapenem Sodium

Abstract: [reaction: see text] A practical synthesis for the large-scale production of the new carbapenem antibiotic, [4R,5S,6S]-3-[[(3S,5S)-5-[[(3-Carboxyphenyl)amino]carbonyl]-3-pyrrolidinyl]thio]-6-[(1R)-1-hydroxyethyl]-4-methyl-7-oxo-1-azabicyclo[3.2.0]hept-2-ene-2-carboxylic acid monosodium salt (ertapenem sodium, 1), has been developed. The synthesis features the novel use of 1,1,3,3-tetramethylguanidine as base for the low-temperature reaction of a thiol, derived from trans-4-hydroxy-L-proline, with the carbapene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…As expected, MALDI-TOF MS of ertapenem showed four peaks: 450 Da (hydrolyzed and decarboxylated ertapenem without sodium), 476 Da (ertapenem without sodium), 498 Da (monosodium salt), and 521 Da (disodium salt) (15). Subsequently, we conducted kinetic studies with strains known to carry carbapenemases (Table 1).…”
mentioning
confidence: 59%
“…As expected, MALDI-TOF MS of ertapenem showed four peaks: 450 Da (hydrolyzed and decarboxylated ertapenem without sodium), 476 Da (ertapenem without sodium), 498 Da (monosodium salt), and 521 Da (disodium salt) (15). Subsequently, we conducted kinetic studies with strains known to carry carbapenemases (Table 1).…”
mentioning
confidence: 59%
“…[113] Further improvements were subsequently made (frequent dosing is still required with meropenem), leading to the 2001 approval of another fully synthetic C1-bmethyl carbapenem, ertapenem (Merck). [114] Carbapenems are not the only fully synthetic b-lactams that have become important antibiotics. In 1981, two research groups independently reported the isolation of monocyclic blactam ("monobactam") natural products from different bacterial strains.…”
Section: Antibacterial Drug Discoverymentioning
confidence: 99%
“…[113] Weitere Verbesserungen im Anschluss (häufige Dosierung ist auch bei Meropenem notwendig) führten 2001 zur Zulassung eines anderen vollsynthetischen C1-b-Methylcarbapenems, Ertapenem (Merck). [114] Carbapeneme sind nicht die einzigen vollsynthetisch hergestellten b-Lactame unter den wichtigen Antibiotika. 1981 beschrieben zwei Forschungsgruppen unabhängig voneinander die Isolierung monocyclischer b-Lactam("Monobactam")-Naturstoffe aus verschiedenen Bakterienstämmen.…”
Section: Vollsynthetische Antibakterielle Chinoloneunclassified